Biological activities of Bambusa vulgaris as medicine potential / Nur Izzah Afifah Azhar - Azhar, Nur Izzah Afifah (2022)
In this study, ethanol and hot water extracts from the shoots of Blumeana var. Luzonensis, Bambusa vulgaris, and S. brachycladum were examined for their phytochemical, antibacterial, and antioxidant capabilities. All of the bamboo shoot extracts mentioned contain cardiac glycosides, flavonoids, saponins, tannins, and terpenoids, per phytochemical study. Only the ethanol extracts of B. blumeana var. Luzonensis and S.brachycladum shoots contained steroid. At 12 and 24 hours of incubation, S. brachycladum shoot ethanol extract had the largest zone of inhibition with 8.68 mm and 8.36 mm, respectively, in an eradicant test against E. coli. At 12 and 24 hours of incubation, S. brachycladum shoot hot water extract created the broadest zone of incubation against S. aureus, with 13.40 mm and 15.32 mm, respectively. Meanwhile with 7.14 mm and 9.97 mm for the protectant test, E. coli created the smallest zone of colonisation in blumeana var. Luzonensis ethanol extract. S. aureus established the smallest zone of colonisation in S. brachycladum shoot ethanol extracts after 12 hours of incubation, measuring 6.28 mm, whereas B. blumeana var. luzonensis ethanol extracts produced the smallest zone in after 24 hours of incubation. Furthermore, antioxidant research revealed that all bamboo shoot extracts were capable of scavenging DPPH radicals. The shoot ethanol extract of B. blumeana var. luzonensis produced the best yield, with 64.80% radical scavenging activity and 27.59 mg AAE/g sample phenolic content. The studied bamboo shoot extracts also contained phytochemicals, which led to their antibacterial and anti-oxidant properties as a result of the findings of this study.